Amplified subtropical stationary waves in boreal summer and their implications for regional water extremes. (14th October 2015) - Yuan, Jiacan; Li, Wenhong; Deng, Yi
Abstract: The linkage between climate change and increased frequency/magnitude of weather extremes remains an open question in the scientific field. Here we investigate such a dynamical linkage by focusing on an amplification trend of the northern subtropical stationary waves found in recent decades. Specifically, we show that in multiple modern reanalysis products, a robust positive trend exists in a wave amplitude index defined through the summer-mean tropospheric stream function field. Pronounced changes in the subtropical atmospheric circulation accompany this wave amplification, including an intensified South Asian monsoon and strengthened subtropical highs over the North Pacific and North Atlantic oceans. Through modifying the characteristics of large-scale moisture transport, these circulation changes are coupled to changes in the regional precipitation amount and the occurrence of water extremes including both droughts and heavy rainfall events. Given this connection, amplified stationary waves have likely contributed to the elevated occurrence probabilities of droughts in the central United States, Mexico, Japan, and northern China, as well as those of heavy rainfall events in South Asia, southeastern China, and the eastern United States. These results suggest that as climate warming continues, the amplification of subtropical stationary waves will increase the risk of water extremes over the above-mentioned regions.